PENGARUH DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS ANYAMAN PURUN DI KECAMATAN HAUR GADING KABUPATEN HULU SUNGAI UTARA - Latte, Jumai; Manan, Abd. (Inovatif Jurnal Administrasi Niaga, 2022)
The purpose of this research was to determine the effect of product design on purchasing decisions for purun woven bag products in Haur Gading District, Hulu Sungai Utara Regency. The type of research used was explanatory. The population and sample in this research were all consumers who knew about purun bags in Hulu Sungai Utara Regency with a total sample of 45 consumers and the sampling technique used accidental sampling technique. The data analysis technique in this study used SPSS statistics 21.0 for windows software. The results of the study proved that product design is significantly positive on purchasing decisions for purun woven bag products. This can be seen from the results of the t test, which is = 0.000 and the value is <0.05, then Ho is rejected and Ha is accepted. With a large influence of 80.9%, indicated that the influence of product design on purchasing decisions for the purun woven bag product is quite large, while 19.1% is the influence of other variables not examined through this study.